Інтертекстуальність як спосіб побудови наративу художньої прози Ніни Бічуї - Римар, Наталія; Rymar, Nataliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано інтертекстуальний потенціал художньої прози Ніни Бічуї. Виділено домінувальні імпліцитні та експліцитні типи міжтекстових відношень з погляду специфіки організації наративу. Охарактеризовано най- продуктивніші форми інтертекстуальності у творчості письменниці – циту- вання, ремінісценції та алюзії. Визначено архітекстуальні ознаки засвідчених у тексті філософських відступів-медитацій, що набувають міжстильових і між- текстових зв’язків. Описано паратекстуальні можливості власне заголовка твору та епіграфа, вказано на автоінтертекстуальність творів.The article analyzes the potential intertextual prose Nina Bichuya. Highlight dominant implicit and explicit types mizhtekstovyh relations in terms of specific organizations narrative. Characterized the most productive form of intertextuality in the work of the writer − citation, reminiscences and allusions. It is found differential features attributive and neatrybutyvnoho citation indexes as intellectual heuristic narration. Arhitekstualni signs pointed certified in the text-philosophical meditation retreats, which have between styles and between the texts ties. Alyuziyni possibilities considered in the context of prose narrative parallels between the wellknown image or text and newly created. An important role has archetypes with traditional and innovative overtones. Reministsentnyy ways of reading intertext described as a set of diverse techniques: introduction to the text of folklore and national-cultural forms of codes, some spots, stories, absorbing different styles and techniques, paraphrasing the source and others. Noted paratekstualnyy own potential title of the work and its epigraph, avtointertekstualnist analyzed prose texts, that is dialogical relations between the author himself, passed through the narrator figure.
Іntertextuality as a Way to Build a Narrative of Prose of Nina Bichuya
Keywords: інтертекстуальність; Ніна Бічуя; наратор; цитування; алюзія; ремінісценція; intertextuality; Nina Bichuya; narrator; citation; allusion; reminiscence